Effect of music intervention on subjective scores, heart rate variability, and prefrontal hemodynamics in patients with chronic pain - Du, Jiahao; Shi, Ping; Fang, Fanfu; Yu, Hongliu (Frontiers in Human Neuroscience, 2022)
Music interventions have been proposed in recent years as a treatment for chronic pain. However, the mechanisms by which music relieves pain are unclear, and the effects of music intervention on physiological indicators in patients with chronic pain remain to be explored. This study aimed to explore whether a music intervention would have effects on subjective pain ratings, heart rate variability, and functional connectivity of the cerebral cortex in patients with chronic pain. A randomized controlled study was conducted on 37 pain patients aged 18-65 years, with the control group receiving usual care, and the intervention group receiving music intervention (8-150 Hz, 50-70 dB) for 30 minutes before bedtime for 7 days on top of usual care. Pain visual analog scale and heart rate variability were used as subjective and objective physiological indices before and after the music intervention, respectively. Changes in oxyhemoglobin and deoxyhemoglobin concentrations in the cerebral cortex were measured by functional near-infrared spectroscopy, and whole-brain correlation analysis was used to quantify the connectivity of prefrontal brain regions associated with the pain response. Results showed that patients with chronic pain in the intervention group had significantly lower visual assessment scale scores, as well as significantly lower overall voluntary mobility during pain episodes, resulting in relatively higher vagal innervation compared to the control group. In addition, connections between the bilateral dorsolateral prefrontal cortex (BA9, BA46) and frontal areas (BA10) were significantly higher in the intervention group. This study demonstrates the effectiveness of the combined application of music interventions with usual care in reducing pain levels in patients with chronic pain and provides insight into the pathological mechanisms of music interventions for analgesia, providing direction for new baseline indicators for quantitative clinical assessment of pain. The study was registered in the Chinese Clinical Trial Registry (No. ChiCTR2100052993).